Quietly hostile eaudiobook Essays. - Irby, Samantha (Books on Tape, 2023)
NEW YORK TIMES BESTSELLER • A GLAMOUR BEST BOOK OF THE YEAR • A hilarious new essay collection from Samantha Irby "engages readers with her characteristic combination of laugh-out-loud moments, heartfelt passages and plenty of awkward experiences.... Quietly Hostile will delight established fans and newcomers alike ( Parade).   “Brilliant and one of the funniest people I’ve ever read.” —Roxane Gay • " The king of sparkling misanthropy and tender, loving dread." — Jia Tolentino "Absolutely hilarious.... If you are feeling down, or you feel like you haven't read anything you've loved in a long time, all you need is Samantha Irby.... She will make you laugh on every page." —Emma Straub, bestselling author of This Time Tomorrow , on The Today Show Samantha Irby’s career has taken her to new heights. She dodges calls from Hollywood and flop sweats on the red carpet at premieres (well, one premiere). But nothing is ever as it seems online, where she can crop out all the ugly parts. Irby got a lot of weird emails about Carrie Bradshaw, and not only is there diarrhea to avoid, but now—anaphylactic shock. She is turned away from restaurants for being inappropriately dressed and looks for the best ways to cope, i.e., reveling in the offerings of QVC and adopting a deranged pandemic dog. Quietly Hostile makes light as Irby takes us on another outrageously funny tour of all the gory details that make up the true portrait of a life behind the screenshotted depression memes. Relatable, poignant, and uproarious, once again, Irby is the tonic we all need to get by.    A BEST BOOK from Vogue, Esquire, PopSugar , Glamour, The Skimm, and more